Analysis Completeness of Outpatient Medical Record Documents Completion Based on Motivation and Compliance with Basic Tasks and The Function of Officers - Sodik, Muhammad Ali; Widyastika, Kharisma Syahda (Journal of Global Research in Public Health, 2020)
In the modern era, the demands of the community health, especially health services, are increasingly high, one of which is the recording of medical records. One of the problems in the world of medical records is the incompleteness of medical record documents. The purpose of research is influence of motivation and compliance of the main tasks and functions of the officer on the completeness of filling outpatient medical record documents at the Tugu Trenggalek Health Center. The research method uses types correlational and cross sectional data collection with a sampling technique that is simple random sampling in order to obtain a total sample of 40 respondents. The data processing technique used is dummy regression analysis. The results showed that out of 40 outpatient medical record documents, 18 documents (45%) are in the low category. Some respondents in Puskesmas Tugu Trenggalek had a moderate motivation level of 22 respondents (55%) and the level of non-compliant respondents was 17 respondents (42.5%). Based on statistical test results obtained a significant value of motivation variable of (0,000 <α 0.05), compliance variable of (0,000 <α 0.05), all dummy variables of the officer function have a significance value (> α 0.05) and a significance value simultaneous testing (0,000 <α 0,005) with an effect of 95.9%. From these results it is known that there is an influence of motivation and compliance of officers on the completeness of outpatient medical record documents at Tugu Trenggalek Health Center. It is necessary to improve performance in order to carry out an analysis of the completeness of outpatient medical record documents. Providing information about the importance of filling out and completing patient medical record data disciplines staff to provide feedback in the form of rewards and punishment so that the outpatient medical record documents are completely filled.